Application of Pig Manure and NPK 16-16-16 Fertilizer on Germination and Yield of Pakcoy (Brassica chinensis L.) - Tuhuteru, Sumiyati; Mahanani, Anti Uni; Rumbiak, Rein Edward Yohanes; Dewi, Yohana Sutiknyawati Kusuma; Tabuni, Endius; Tabo, Opapur; Doga, Konius; Wenda, Endison; Lengka, Mariana; Himan, Rusina (P3KM Politeknik Pertanian Negeri Samarinda, 2023)
Pakcoy is one of the most popular vegetables for taste and content nutrition; with system-classified cultivation it is easy and efficient. For it is needed to trial activities related comparison between system cultivation in a manner organic, non-organic with system cultivation without fertilizer (is natural) through the utilization compound NPK fertilizers and fertilizers dirt cattle obtained pork from a farm owned by the farmer. The research going on together with Kosabangsa Project (Collaboration Together to Build Nation) phase Pilot Project Petra Baliem STIPER Wamena with the University of Tanjungpura Pontianak, in Jayawijaya. Test This is arranged in the form Draft Random Complete (RAL) with repetition divided three times in treatment A (without fertilizer/traditional), treatment B (compound NPK), and treatment C (Fertilizer dirt pig). The results show exists different influences one the same other to growth sprouts plant pakcoy tested try, i.e., treatment C had an effect real so real in increase growth sprouts plant pakcoy; meanwhile, treatment B showed influence real to plant fresh weight. Furthermore, treatment A also has an effect seen only in the speed parameter growth, which is expected to be caused Because the elongation process occurs in plants, which is a physiological process plants obtain source energy from the sunlight.